The Effect of Coal Fly Ash Crystallinity toward Methyl Violet Adsorption Capacity - Widi Astuti; I Made Bendiyasa; Endang Tri Wahyuni; Agus Prasetya (ASEAN Journal of Chemical Engineering, 2010)
Coal fly ash (CFA) generated by coal-based thermal power plants is mainly composed of some oxides having high crystallinity, like quartz and mullite. In this study, the effect of CFA crystallinity toward methyl violet (MV) adsorption capacity was investigated. To decrease crystallinity of CFA, the solution of sodium hydroxide (NaOH) of 1-7 M was used to treat CFA at various temperatures and reflux time. Then, to evaluate the effect of NaOH-treated CFA with respect to adsorption capacity, the original and NaOH-treated CFA were tested its MV adsorption capacity in batch experiments. Original or NaOH-treated CFA was contacted with 50 mL of MV solution at temperature of 26oC. The effects of contact time, pH of solution, adsorbent dose and initial concentration of dye on the adsorption of MV were investigated. The results show that CFA treated with low NaOH concentration (1-3 M), temperature of 60oC and 2 hours reflux time, the crystallinity of quartz and mullite decreases, but its capacity on MV adsorption increases from 34% to 97%. At higher NaOH concentration (>3M), in the range of studied reflux temperature and time, it is found that decreasing quartz and mullite crytallinity are followed by a hydroxysodalite formation which causes the decreasing of MV adsorption from 97% to 83%. The highest adsorption capacity of NaOH-treated CFA was found 1.24 x 10-5 mol g-1. Adsorption kinetics of MV onto NaOH-treated CFA could be approximated with a pseudo second order kinetic model with the rate constant was 3.2 x 103 g mol-1 min-1.